Feed intake, gastrointestinal system and body composition in reindeer calves fed early harvested first cut timothy silage (Phleum pratense) - Norberg, Harri J.; Mathiesen, Svein D. (Rangifer, 1998)
Early harvested first cut (EFC) timothy silage was fed to five reindeer calves (Rangifer tarandus tarandus L.) taken from their natural summer pasture and brought to Tromsø for feeding trial. The calves were housed indoors in metabolism cages and fed EFC timothy silage ad lib. during the trial, which lasted from late November 1994 until the end of February 1995, when animals subsequently were slaughtered. Daily feed intake, gastrointestinal (GI) anatomy, body weight and body composition of the animals were examined. Timothy silage {Phleum praténse) was harvested 21 June, 1994 in Tromsø, prewilted and stored as round bales containing 97% leaves. The EFC silage contained 42.1% dry matter (DM), and 18.1% crude protein, 20.7% cellulose, 16.9% hemicellulose and 28.0% water soluble carbohydrates (WSC) of DM. Mean feed intake (DM) 24 hours after the trial started (day 1) was 9-4 g/kg body mass (BM) (S.D.+ 3-9), while the mean daily DM intake during days 15-74 comprised 24.2 g/kg BM (S.D.+ 6.1). All animals except one gained body weight during the trial. The median (range) BM at start and at slaughter was 48.5 kg (34.5¬58.0 kg) and 50.0 kg (42.0-53.5 kg), respectively. Median (range) carcass weight % of BM was 58.0% (51.2-58.7%) and muscle index value 0.0132 (0.0106-0.0176). The median reticulo-rumen (RR) content wet weight (WW) was 4601 g (range 2697-5000 g) comprising 9.3% of the BM, and 85.1% of the total gastrointestinal wet weight content. The median (range) gastrointestinal tract weight was 14.1% of BM (10.7-16.4%). Based on feed intake during the trial and body composition at slaughtet we conclude that first cut timothy silage is suitable as emergency feed to reindeer, as long as it is harvested in early growth stage with high proportion of leaves.